Urinary stones as the initial presentation in a child with late-onset molybdenum cofactor deficiency type B: a case report and review of literature - Abdelrahim A. Sadek; Mohammed A. Aladawy; Rofaida M. Magdy; Mohammed Fawzy Fouad; Tarek M. M. Mansour; Eman Fathalla Gad; Elsayed Abdelkreem (Egyptian Journal of Medical Human Genetics)
Abstract Background Molybdenum cofactor deficiency (MoCD) is a rare genetic disease primarily affecting the nervous system. While xanthinuria is a typical feature of MoCD, xanthine stones have been rarely described. Herein, we report the first case of MoCD who presented with urinary xanthine stones before the onset of neurological manifestations. Case presentation A 2-year-old girl, born to consanguineous Egyptian Arab parents with a family history of a brother’s death after renal stone surgery, exhibited normal development during infancy. However, her mother noticed recurrent mustard-yellow stones in her diapers. At the age of 12 months, the girl experienced acute gastroenteritis followed by a severe encephalopathic episode, which evolved into developmental impairment, spastic quadriparesis, dystonia, aphasia, and failure to thrive. Brain magnetic resonance imaging revealed signal abnormalities in the basal ganglia as well as cerebral atrophic changes. Abdominal ultrasound exhibited multiple kidney stones obstructing the left pelvicalyceal system with back pressure changes. Laboratory tests showed hypouricemia, xanthinuria, and positive urine sulfite. Whole exome sequencing identified a homozygous variant (NM_176806.3:c.3G > A) in the MOCS2 gene, confirming a diagnosis of MoCD type B. Conclusion This case report expands the phenotypic spectrum of MoCD and underscores the diagnostic importance of urinary xanthine stones, which may precede neurological manifestations in patients with the late-onset phenotype.